Art, literature and affection in early childhood education: creating illustrated stories with future teachers - Caeiro Rodríguez, Martín (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
A project is proposed to the students of the Degree in Early Childhood Education to create an illustrated story and its subsequent narration and audio visual recording in pairs, as well as the design of an illustration workshop and the testing of evaluation instruments. We applied visual arts based research and visual anthropology to analyse the experiences. The results reveal the teacher training students’ understanding of the peculiarities of the children they will be working with, as well as the importance of artistic expression and language in their training.